2008
DOI: 10.1080/00365520701579662
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the mucus barrier of the rat during 5-fluorouracil-induced gastrointestinal mucositis

Abstract: The activation of mucus cells in the jejunum, if appropriately manipulated, could lead to more effective prevention of CT-induced GI mucositis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Mucin is involved in protection of the mucosa and the maintenance of normal intestinal flora . Cavitated goblet cells (goblet cells which have released mucins through exocytosis) and Muc4 expression increased in the jejunum of rats treated with irinotecan or 5‐fluorouracil (5‐FU), but mucin levels decreased in the rat jejunum and colon after 5‐FU treatment . The increased number of goblet cells reported here may be related to an overproduction to protect the mucosa .…”
Section: Discussionmentioning
confidence: 71%
“…Mucin is involved in protection of the mucosa and the maintenance of normal intestinal flora . Cavitated goblet cells (goblet cells which have released mucins through exocytosis) and Muc4 expression increased in the jejunum of rats treated with irinotecan or 5‐fluorouracil (5‐FU), but mucin levels decreased in the rat jejunum and colon after 5‐FU treatment . The increased number of goblet cells reported here may be related to an overproduction to protect the mucosa .…”
Section: Discussionmentioning
confidence: 71%
“…Mucins have been shown to be associated with mucositis [22,23,54,55,56]. Dark Agouti (DA) rat models of mucositis have been used to determine a significant association with mucin secretion and expression [22,23].…”
Section: Effects Of Chemotherapymentioning
confidence: 99%
“…Furthermore, a Wistar rat model of 5-FU-induced mucositis (5 × 50 mg/kg) caused a significant ( p < 0.05) decrease in mucin levels compared to controls in the jejunum and colon [55], suggesting mucin expression was decreased. Mucin expression has also been shown to be significantly ( p < 0.05) decreased in a Wag/Rij rat model of methotrexate (MTX) induced mucositis (2 × 10 mg/kg), with Muc 2 expression decreased significantly from 72 h to 44 h following MTX administration [56].…”
Section: Effects Of Chemotherapymentioning
confidence: 99%
“…Our previous studies showed quantitative and qualitative changes in GI mucin in normal and diseased animals, as well as in humans, and demonstrated the importance of mucin in the GI mucosal barrier [1518]. We have also established several monoclonal antibodies (mAbs) that react with mucin synthesized and secreted by specific mucus-producing cells of the rat GI mucosa [1820]. …”
Section: Introductionmentioning
confidence: 99%